Benjamin's passages : dreaming, awakening - Gelley, Alexander (New York : Fordham University Press, 2015)
In transposing the Freudian dream work from the individual subject to the collective, Walter Benjamin projected a 'macroscosmic journey' of the individual sleeper to 'the dreaming collective, which, through the arcades, communes with its own insides'. This book examines the figurative status of sleeping and awakening within the allegorical structure of The Arcades Project and in Benjamin's thought more broadly.
Introduction -- Contexts of the aesthetic -- Epigones in the house of language: Benjamin and Kraus -- Benjamin on atget: empty streets and the fading of aura -- Entering the passagen -- Citation as incitation: the political agenda of the passagenarbeit -- Messianism, "weak" and otherwise -- Forgetting, dreaming, awakening.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Benjamin, Walter, -- 1892-1940 -- Criticism and interpretation; Benjamin, Walter, -- 1892-1940 -- Criticism and interpretation; Benjamin, Walter, -- 1892-1940; LITERARY CRITICISM -- European -- German; PHILOSOPHY -- General; Languages & Literatures; Germanic Literature; Criticism, interpretation, etc